2015
DOI: 10.1177/0733464815608493
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records in Long-Term Care: Staff Perspectives

Abstract: As long-term post-acute care (LTPAC) settings continue to increase their adoption of electronic health records (EHRs), it is important to learn from end users currently working with the technology to identify clinical implications and opportunities to improve systems and surrounding processes. This study utilized one-on-one interviews of direct care nurses ( n = 20) in a Midwest United States LTPAC setting to describe patterns of use, and areas to improve. The majority of respondents evaluated the EHR as easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…Furthermore, staff can quickly move from one resident's record to another, and multiple staff members are able to access records at the same time. 32 The processes of data distribution, storage, and retrieval were also described as more efficient, 5,19,31,32,[34][35][36] and the presence of a spellcheck saves time on proofreading. 37 Moreover, increased legibility has meant that staff are no longer forced to call doctors to clarify information that was previously handwritten, often causing time delays.…”
Section: Time For Direct Carementioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, staff can quickly move from one resident's record to another, and multiple staff members are able to access records at the same time. 32 The processes of data distribution, storage, and retrieval were also described as more efficient, 5,19,31,32,[34][35][36] and the presence of a spellcheck saves time on proofreading. 37 Moreover, increased legibility has meant that staff are no longer forced to call doctors to clarify information that was previously handwritten, often causing time delays.…”
Section: Time For Direct Carementioning
confidence: 99%
“…37 Moreover, increased legibility has meant that staff are no longer forced to call doctors to clarify information that was previously handwritten, often causing time delays. 35 Florczak et al 33 found that portable, handheld devices increased efficiency as they enabled staff to access and record data at the point of care. However, in a separate study, some staff felt that bedside technology was time-consuming, and as a result, they were found to be documenting at the end of their shift, and some documenting before care had been provided.…”
Section: Time For Direct Carementioning
confidence: 99%
See 3 more Smart Citations